2020
DOI: 10.1155/2020/4807179
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Systemic Inflammation Exacerbates Neurotoxicity in a Parkinson’s Disease Model

Abstract: Systemic inflammation is a crucial factor for microglial activation and neuroinflammation in neurodegeneration. This work is aimed at assessing whether previous exposure to systemic inflammation potentiates neurotoxic damage by the neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and how chronic systemic inflammation participates in the physiopathological mechanisms of Parkinson’s disease. Two different models of systemic inflammation were employed to explore this hypothesis: a single administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 103 publications
(128 reference statements)
3
15
0
Order By: Relevance
“…Thus, the M. tb -induced neuroinflammation is probably an indirect effect of lung inflammation. Similar results were found in a study that used multiple low doses of LPS administration; it found that systemic inflammation generated by LPS induces a significant rise in the brain levels of TNFα, IL-6, IL-10 and TGFβ [ 40 ]. Similar results were found in murine models infected with Plasmodium falciparum [ 41 ] or coinfected with Toxocara canis and Toxoplasma gondii [ 42 , 43 ] that induced an increase in TNFα, IFNγ, IL10 and IL4 brain production following infection with these parasites.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, the M. tb -induced neuroinflammation is probably an indirect effect of lung inflammation. Similar results were found in a study that used multiple low doses of LPS administration; it found that systemic inflammation generated by LPS induces a significant rise in the brain levels of TNFα, IL-6, IL-10 and TGFβ [ 40 ]. Similar results were found in murine models infected with Plasmodium falciparum [ 41 ] or coinfected with Toxocara canis and Toxoplasma gondii [ 42 , 43 ] that induced an increase in TNFα, IFNγ, IL10 and IL4 brain production following infection with these parasites.…”
Section: Discussionsupporting
confidence: 86%
“…Our results showed that after two months of infection, the permeability of BBB increased. Similar results have been found with the administration of LPS, where chronic systemic inflammation by itself affects BBB integrity [ 40 , 53 ]. Furthermore, metabolic syndrome and the resulting insulin and leptin resistance and hyperglycaemia have pro-inflammatory effects with profound consequences on the BBB [ 54 ].…”
Section: Discussionsupporting
confidence: 85%
“…It has recently been reported that obesity is associated with a low-grade inflammatory state [9], [10], [27]. Such a condition triggers systemic inflammation which is an important factor for microglial activation and neuroinflammation in neurodegeneration [11]. This may happen due to excess macronutrients in adipose tissue that stimulate the release of pro-inflammatory mediators, such as TNF-α and IL-6 and reduce the production of anti-inflammatory agents, such as adiponectin [12].…”
Section: Discussionmentioning
confidence: 99%
“…Potential mechanisms in these changes include inflammation and vascular and metabolic changes [8]. Recently, obesity has also been associated with a low-grade inflammatory state [9], [10], [11]. This condition triggers systemic inflammation which becomes an important factor for microglial activation and neuroinflammation in neurodegeneration [12].…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that the intravenous injection of indol, which is similar to the product of bacterial metabolism of tryptophan, allows overcoming the BBB [ 111 ]. Neuro-inflammatory effects of LPS act through TLR activation in peripheral tissues, causing secondary effects in the nervous system by BBB-positive pro-inflammatory cytokines [ 112 , 113 , 114 ].…”
Section: The Neuroimmune Axis: Microbiota–intestine–brain-cvdmentioning
confidence: 99%